Sucrose Formulated Recombinant Human Antihemophilic Factor VIII Is Safe and Efficacious for Treatment of Hemophilia A in Home Therapy - Abshire, T. C.; Brackmann, H.-H.; Scharrer, I.; Hoots, K.; Gazengel, C.; Powell, J. S.; Gorina, E.; Kellermann, E.; Vosburgh, E.; and the International Kogenate-FS Study Group (Thrombosis and Haemostasis, 2000)
To add an increased level of safety to antihemophilic factor replacement therapy, a full-length, recombinant Factor VIII (rFVIII) product has been developed without human-derived plasma proteins during purification and formulation and using an additional solvent/detergent viral inactivation step. This first clinical trial of a sucrose-formulated full-length rFVIII (rFVIII-FS) was conducted in previously treated patients (≥100 prior exposure days) with severe (<2% FVIII) hemophilia A in North America (NA) and Europe (EU). Pharmacokinetic profiles for rFVIII-FS were compared with those of currently licensed rFVIII product (Kogenate®) in 35 patients. Safety and efficacy during home therapy were evaluated in 71 patients. The new formulation displayed a pharmacokinetic profile similar to that of rFVIII. Patients on home therapy received a cumulative total of 11,867 exposure days, 12,546 infusions, and 22,443,694 IU of rFVIII-FS. Of 2585 bleeds, 93.5% were treated with 1-2 infusions and 80.5% of responses were rated as excellent or good. No evidence of de novo inhibitor formation was observed. Only 0.27% of infusions were associated with any drugrelated adverse event. Except for an episode of intermittent chest pain with palpitations which ceased after treatment with analgesics, associated adverse events were mild or moderate. Overall, rFVIII-FS provided excellent hemostatic control, was well-tolerated, and caused no significant adverse effects, thus demonstrating safety and efficacy for treatment of bleeds in patients with hemophilia A.
Keywords: Hemophilia A; recombinant Factor VIII; full-length rFVIII